Material–Psychosocial–Behavioral Aspects of Financial Hardship: A Conceptual Model for Cancer Prevention - Tucker-Seeley, Reginald D (Gerontologist, 2019)
Risk of cancer increases with age; and socioeconomic factors have been shown to be relevant for (predictive of) cancer risk-related behaviors and cancer early detection and screening. Yet, much of this research has relied on traditional measures of socioeconomic status (SES) to assess socioeconomic circumstances, which limits our understanding of the various pathways through which the socioeconomic environment affects cancer risk. Research on hardship and health suggests that concepts of financial hardship can uncover socioeconomic factors influencing health behaviors over and above traditional SES measures. Thus, consistently including measures of financial hardship in cancer prevention research and practice may help us further explicate the pathway between socioeconomic circumstances and cancer risk-related behaviors and cancer screening among older adults and help us identify intervention and policy targets. We present a conceptual model of financial hardship that can be applied to cancer prevention research among older adults to provide guidance on the conceptualization, measurement, and intervention on financial hardship in this population. The conceptual model advances a research agenda that calls for greater conceptual and measurement clarity of the material, psychosocial, and behavioral aspects of the socioeconomic environment to inform the identification of potentially modifiable socioeconomic factors associated with cancer risk-related behaviors among older adults.